تابعية عمليّة تشكل النويدات لخواص الوسط البلازمي (Latakia University Journal -Basic Sciences Series, 2018)
تعتبر دراسة عمليّة تشكل النويدات في البلازما الدخانية الحرارية (المتشكلة في أثناء احتراق المسحوق المعدني في اللهب الطباقي ثنائي الطور) ذات أهميّة كبيرة في مجالات تكنولوجية متعددة، إذ يؤدي تفاعل الجسيمات المتكاثفة في البلازما الدخانية إلى تغيّر مستوى الخلفية الحياديّة في البلازما، مما يؤثر في أبعاد نويدات الخرج. وقد تمت دراسة تأثير درجة حرارة البلازما في تشكّل النويدات التي تفسّر تغيّر معامل الشدّ السطحي والطاقة الحرة المرتبطة بشحنة النويدات المتشكلة. The study of the nucleation process of thermal plasma smoke (formed in a laminar two-phase flame of a metal powder) plays a great role in multiple technology of areas. It is shown, that collective interaction of the condensed grains in smoky plasma leads to change of a neutral phon level in the plasma and influences the critical sizes of particles. The influence of plasma temperature on the nucleation change the coefficient of surface tension and free energy, which is related to the charge of the particle.